2015
DOI: 10.1063/1.4936553
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical discovery of stable structures of group III-V monolayers: The materials for semiconductor devices

Abstract: Group III-V compounds are very important as the materials of semiconductor devices. Stable structures of the monolayers of group III-V binary compounds have been discovered by using first-principles calculations. The primitive unit cell of the discovered structures is a rectangle, which includes four group-III atoms and four group-V atoms. A group-III atom and its three nearest-neighbor group-V atoms are placed on the same plane; however, these connections are not the sp2 hybridization. The bond angles around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…This small imaginary acoustic phonon appearing near the zone center do not correspond structural instability. The negligible imaginary frequency of the acoustic mode is a numerical error, arising due to violation of translational invariance in approximated calculation [46,47]. The phonon dispersion plots, hence confirms the structural stability of the both the phases.…”
Section: Stabilitysupporting
confidence: 61%
“…This small imaginary acoustic phonon appearing near the zone center do not correspond structural instability. The negligible imaginary frequency of the acoustic mode is a numerical error, arising due to violation of translational invariance in approximated calculation [46,47]. The phonon dispersion plots, hence confirms the structural stability of the both the phases.…”
Section: Stabilitysupporting
confidence: 61%
“…We note that for each n the calculated cohesive energies of tetragonal and hexagonal armchair structures are higher than those of DLHC and haeckelite structures. It is thus concluded that the structures proposed in previous calculations 12) are always metastable and hardly formed even in the 2D limit. Although, L h for DLHC and haeckelite structures depends on the constituent elements, similar thickness dependence in the cohesive energy is often found in A N B 8−N thin film as shown in Figs.…”
mentioning
confidence: 55%
“…As well known, 3D ZnO bulk exhibits a diversity in the crystalline phase, as the two isotropic cubic of rocksalt and zinc blende phases, and an isotropic hexagonal wurtzite phase [31]. In this regard, 2D ZnO monolayer was also expected to show a variety of configurations, as that of some III-V group 2D materials which have been demonstrated in theory [56,57]. Herein, five typical structures for the binary compound monolayer named as Planar (Plan), Tile, Double-layer honeycomb (Dlhc), Zigzag (Zigz) and Puckered (Puck) were built to be the primitive 2D ZnO candidates with the space group of P-6m2 (187), Pmm2 (25), P-3m1 (164), Pmn2 1 (31) and Pmn2 1 (31) [7,57,58], respectively.…”
Section: Crystal Structures Of 2d Zno Systemmentioning
confidence: 77%